The Role Of Job Rotation And Training On Competence With Job Satisfaction As Mediation - Mohammad Mu'zi Masyfa Audzillah; Faisol Faisol; Vivin Maharani Ekowati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to examine and analyse the effect of job rotation and training on employee competence, with job satisfaction serving as a mediator. This study employs a quantitative approach with a population of 35 employees at PT Ababil Widjaya Lestari, which is also used as a sample, utilising a saturated sampling technique. Data collection was conducted using a questionnaire with a 1-5 Likert scale. Data analysis employed the Partial Least Squares Structural Equation Modelling (PLS-SEM) method, utilising the SmartPLS software. The results showed that job rotation had a positive and significant effect on employee competence. Conversely, training did not have a positive and significant effect. Furthermore, job satisfaction was also unable to mediate the effect of job rotation and training on employee competence. These findings indicate that competence in the construction sector is more influenced by direct work experience through job rotation than by training programs.